Managing Knee Pain Through Acupuncture: Evidence from Bandung Clinical Practice - I Gusti Ngurah Dwi Wiryawan; Leny Chandra; Puspo Wardoyo (Malahayati Nursing Journal, 2026)
ABSTRACT Knee joint pain is a common musculoskeletal complaint that may lead to functional limitation and reduced daily comfort. In Indonesia, acupuncture is widely applied as a non-pharmacological therapy; however, reports from routine clinical practice remain limited. Objective: This study aimed to describe the implementation of acupuncture care and its outcomes in managing knee joint pain in an acupuncture therapist practice in Bandung. Methods: This study used a qualitative case study design. A patient with chronic knee joint pain underwent acupuncture treatment biweekly for ten sessions. Data were collected through clinical observation, patient-reported pain intensity measured by the Visual Analogue Scale (VAS), and the documentation of functional changes during treatment. Results: The pain level dropped steadily from VAS 7 at the beginning to VAS 0 at the end. The patient also said that their daily activities were easier whilst there were no negative effects. According to Traditional Chinese Medicine, the problem was cold–damp Bi syndrome, which helped choose the right points and treatment plan. Conclusion: Acupuncture care based on Traditional Chinese Medicine pattern differentiation showed clear pain relief and improved function in knee joint pain, which supports its use in everyday clinical settings. Keywords: Acupuncture, Knee Joint Pain, Cold–Damp Bi Syndrome, Clinical Case.